2014
DOI: 10.1038/pr.2014.204
|View full text |Cite
|
Sign up to set email alerts
|

Maternal LC-PUFA status during pregnancy and child problem behavior: the Generation R Study

Abstract: Background: Omega 3 (n-3) and 6 (n-6) long-chain polyunsaturated fatty acids (LC-PUFAs) and the n-3:n-6 ratio are important for brain development. Whether maternal LC-PUFA status during pregnancy affects risk of problem behavior in later childhood is unclear. Methods: Within a population-based cohort, we measured maternal plasma docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and arachidonic acid (AA) concentrations and n-3:n-6-ratio in mid-pregnancy. Child emotional and behavioral problems at 6 y of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Several cohort studies reported a negative relation between maternal n-6/n-3 PUFAs status and infant and child neurodevelopment assessed by various tests [4, 79] and these reports partly confirmed our results. The Seychelles Child Development Nutrition Study (SCDS) [4] reported that maternal n-6/n-3 PUFAs in serum was negatively associated with the BSID-II PDI at 9 months of age but not at 30 months.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several cohort studies reported a negative relation between maternal n-6/n-3 PUFAs status and infant and child neurodevelopment assessed by various tests [4, 79] and these reports partly confirmed our results. The Seychelles Child Development Nutrition Study (SCDS) [4] reported that maternal n-6/n-3 PUFAs in serum was negatively associated with the BSID-II PDI at 9 months of age but not at 30 months.…”
Section: Discussionsupporting
confidence: 91%
“…The EDEN mother-child cohort in France showed that maternal dietary n-6/n-3 PUFAs intakes among never-breastfed children were negatively associated with the MacArthur Communicative Development Inventory (CDI) at 2 years of age and with the ASQ at 3 years of age [8], while the n-6/n-3 PUFAs in colostrum among breastfed children was negatively associated with the ASQ at 3 years of age [9]. Recently, the Generation R study in the Netherlands [7] demonstrated that a higher maternal plasma n-3/n-6 PUFAs was associated with fewer emotional problems in children at 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventional studies failed to find evidence that prenatal fish-oil (and folic acid) supplementation may influence the cognitive development of children at 6.5 y of age, but a high DHA in maternal erythrocytes at delivery was associated with a Mental Processing Composite Score higher than the 50th percentile in the offspring [25]. Also, associations of maternal LC-PUFA status with child emotional and behavioral problems were found in an epidemiologic study [26]. Nowadays, special formulae for the treatment of CMA are not in line with these characteristics of HM (Table 1).…”
Section: –16: Many More Reasons For Considering Breastfeeding As mentioning
confidence: 99%
“…According to the abovementioned study, higher AA levels were identified in children with behavioral problems. A high maternal DHA and w-3:w-6 ratio were associated with few children with emotional problems [5].…”
Section: Current Evidence Of N-3 Pufas In Health and Diseasementioning
confidence: 96%